PSVIII-11 Eimeria management for recently transported Holstein heifers using essential oils, anti IL-10 or monensin. (30th November 2020) - Nolden, Cherrie; Akins, Matt; Grisham, Abbey; Schaefer, Dan; Cook, Mark
Abstract: Eimeria prevention in dairy heifers is challenging. Possible tools beyond the common practice of feeding an ionophore include polyphenolic compounds in essential oils (cinnamaldehyde, thymol, oregano oil) and binding interleukin-10 (IL-10) to reduce Eimeria's host immunotolerance strategy. Holstein heifers (160 total; 12–14 wk old) were randomly assigned to one of 5 treatments: 160 mg/head/d of sodium monensin (MON), 1100 mg/head/d of antibody to IL-10 during wk 3–4 (aIL-10), 10 g/head/d of a blend of essential oils (EO), egg control without antibodies to IL-10 (EC), or negative control (NC). Calves were grouped 8 per pen with 4 blocks of 5 pens and FEC averaged by pen before analysis. We evaluated treatment effects on the fecal egg counts (FEC) of E. bovis, E. zurnii and E. auburnesis. Fecal counts were conducted biweekly using FLOTAC technique for 10 wk. Effects were analyzed with a mixed model ANOVA in SAS with repeated measures and ranked for normality. Total FEC prevalence was absent at wk 0, with greater prevalence at wk 4 and 6 for all treatments except MON (P < 0.05), and there were no differences among treatments in positive prevalence by wk 8 and 10 (P > 0.10). There was no difference between NC and MON treatments for wk 6, 8 and 10 in E. bovis, wk 2 and 4 for E. zurnii, and wk 2 and 4 for E. auburnesis (P > 0.05), which is evidence of reduced monensin efficacy or excessive environmental Eimeria load. EO and aIL-10 FEC were also not different than MON counts at multiple timepoints (P > 0.05). Overall, this shows potential monensin resistance after extended exposure (6–8 wk) to high environmental loads of Eimeria and similar FEC between monensin treated calves and those treated with EO or aIL-10.